2021
DOI: 10.1093/eurpub/ckaa227
|View full text |Cite
|
Sign up to set email alerts
|

Association between health literacy and colorectal cancer screening behaviors in adults in Northwestern Turkey

Abstract: Background In this study, aimed to determine the frequency of participation in colorectal cancer (CRC) screenings, the factors affecting participation and the association between CRC screening behaviors and health literacy (HL). Methods This community-based cross-sectional study was carried out with 408 people residing in Kirklareli, a province in Northwestern Turkey, between August and November 2019. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 21 publications
3
12
0
Order By: Relevance
“…Indeed, multiple studies have found that greater health literacy regarding colon cancer can increase colonoscopy rates and healthseeking behavior more broadly, potentially reducing delays in care. [40][41][42][43] Although our models adjusted for sociodemographic factors such as educational attainment, income, and insurance status, social disadvantage in the form of increased exposure to health risks and reduced access to healthy behaviors and care resources may help explain the disparities we found in stage-at-presentation and time-tosurgery delays, as well as provide avenues for policy action.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, multiple studies have found that greater health literacy regarding colon cancer can increase colonoscopy rates and healthseeking behavior more broadly, potentially reducing delays in care. [40][41][42][43] Although our models adjusted for sociodemographic factors such as educational attainment, income, and insurance status, social disadvantage in the form of increased exposure to health risks and reduced access to healthy behaviors and care resources may help explain the disparities we found in stage-at-presentation and time-tosurgery delays, as well as provide avenues for policy action.…”
Section: Discussionmentioning
confidence: 99%
“…In a multicenter study, the average participation rate in colorectal cancers scans in the Asia-Paci c region was 27%, with the highest participation rate in the Philippines and the lowest in India [40]. Similarly, in some studies conducted with adults, the frequency of participation in the FBOT was twice as high as in colonoscopy scans [41,42]. Various reasons reduce participation in cancer screenings, and it is vital to determine the relevant factors to solve these reasons.…”
Section: Resultsmentioning
confidence: 99%
“…Although Zamorano et al ( 14 ) found no association, Thompson et al ( 43 ) reported results that corroborated our findings, suggesting that physical activity was associated with increased participation rates. In this regard, it is believed that people who engage in healthy habits would be responsive to early screening procedures for disease control ( 44 ). Finally, findings from our study, as well as others ( 41 , 45 ), have shown that current smoking is significantly related with a reduced likelihood of screening.…”
Section: Discussionmentioning
confidence: 99%